How we treat octogenarians with brain metastases - Nieder, Carsten; Andratschke, Nicolaus H.; Grosu, Anca L. (Frontiers in Oncology, 2023)
Biologically younger, fully independent octogenarians are able to tolerate most oncological treatments. Increasing frailty results in decreasing eligibility for certain treatments, e.g., chemotherapy and surgery. Most brain metastases are not an isolated problem, but part of widespread cancer dissemination, often in combination with compromised performance status. Multidisciplinary assessment is key in this vulnerable patient population where age, frailty, comorbidity and even moderate additional deficits from brain metastases or their treatment may result in immobilization, hospitalization, need for nursing home care, termination of systemic anticancer treatment etc. Here, we provide examples of successful treatment (surgery, radiosurgery, systemic therapy) and best supportive care, and comment on the limitations of prognostic scores, which often were developed in all-comers rather than octogenarians. Despite selection bias in retrospective studies, survival after radiosurgery was more encouraging than after whole-brain radiotherapy. Prospective research with focus on octogenarians is warranted to optimize outcomes.